Investigations on the effect of halloysite nanotubes loading on the physicochemical properties of cellulose acetate/polysulfone asymmetric membrane - Nurul Ain Arjuna; Noor Maizura Ismail; S. M. Anisuzzaman; Rachel Fran Mansa; Murni Sundang; Akhtar Razul Razali (eXPRESS Polymer Letters)
Membrane-based gas separation offers practical advantages for hydrogen (H2) and carbon dioxide (CO2) separation for steam methane reforming units. Modification of membrane materials can optimize membrane performance. In this study, the central focus is on investigating the effect of different loadings of halloysite nanotubes (HNTs) (0, 0.5, 1.0, 1.5, and 2.0 wt%) incorporated into a blend of cellulose acetate (CA) and polysulfone (PSF) polymers with the aim of improving the membrane properties. The Fourier transform infrared spectroscopy-attenuated total reflectance (FTIR-ATR) results confirmed that the primary functional groups of PSF and CA remained intact upon HNTs incorporation, with no distinct HNT peaks altering the main chemical functionalities. Field emission scanning electron microscopy- energy dispersive X-ray spectroscopy (FESEM-EDX) analyses showed that low concentrations of HNTs (0.5 wt%) improved surface smoothness and reduced macrovoids, beneficial for gas separation. Cross-sectional images of FESEM micrographs showed no evidence of obvious agglomeration, suggesting a good dispersion of HNTs. From the X-ray diffraction (XRD) analysis, all the membrane samples retained an amorphous structure, indicating that the incorporation of HNT has less effect on the polymer chain properties of the membranes.